PROBLEM BASED LEARNING (PBL) MODEL: CONCEPT, CHARACTERISTICS, AND ITS IMPLICATIONS IN SCIENCE LEARNING - Sulis Rahmatia; Fitratunisyah (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2025)
This study examines the concept, characteristics, and implications of Problem-Based Learning (PBL) in science learning, with a focus on its alignment with the Independent Curriculum in Indonesia. The background of the study is based on the need for an innovative learning model that can develop critical thinking skills, science literacy, and 21st-century competencies in students, while also overcoming the limitations of conventional teacher-centered approaches. Through a literature review method, this study synthesizes findings from academic books, national and international journals, and other relevant sources to analyze the theoretical framework, practical applications, and challenges of PBL in science learning. The results of the study revealed the student-centered nature of PBL which emphasizes authentic problem solving, collaborative learning, and the role of teachers as facilitators. The main findings showed the effectiveness of PBL in improving critical thinking skills, problem solving, and student engagement in science learning. This study also confirmed the alignment of PBL with the Independent Curriculum, especially in supporting differentiated learning and the development of the Pancasila Student Profile. However, challenges such as teacher readiness, limited resources, and the need for technology integration were identified as barriers to implementation. In conclusion, PBL offers a transformative approach to science education that equips students with essential skills for future challenges. The study recommends teacher professional development, further research on the long-term impact of PBL, and policy support to facilitate its widespread adoption. This study contributes to the theoretical and practical understanding of PBL, and serves as a reference for educators and policy makers in improving the quality of science learning in Indonesia.